Effects of some essential oils on growth performance and Campylobacter jejuni in broilers - Abd EL-Dayem, Ghada A.; Shalaby, Marwa; Elkenawy, Mona E. (Journal of Advanced Veterinary Research, 2024)
The current study was carried to investigate the prevalence of Campylobacter jejuni in broiler chicks in Dakhalia province. Besides, the effects of carvacol and thymol essential oils (EO), as a continuous drinking water treatment for protection against Campylobacter jejuni challenge in commercial broiler chickens were assessed. Four hundred and fifty samples were collected from 50 healthy bird, 100 freshly dead birds and 100 diseased birds. Out of 450 examined samples, 22.44 % (101Ì¸450) were positive for Campylobacter jejuni. These isolates were sensitive for neomycin, amoxicillin and ceftriaxone. Random assignment of 180 one-day old chicks into 6 groups (30 birds/group in 3 replicates) arranged as follows: G1 as non-challenged group, G2 was challenged with C. jejuni while G3, and G4 were challenged with C. jejuni and continuously supplemented with carvacol and thymol, respectively, in drinking water from day 7. G5 was challenged with C. jejuni and had the two essential oils continuously in drinking water from day 7. G6 was challenged with Campylobacter jejuni and treated with neomycin (15 mg/kg B.W). Our results showed that the combination of essential oils was more effective in mitigating the devastating effects of Campylobacter jejuni challenge in broilers than using one EO alone. Growth performance represented by body weight gain, and feed conversion ratio were significantly (p<0.05) improved. Campylobacter jejuni shedding was reduced in the challenged treated groups. Also, the biochemical profile was improved. In addition, the level of the pro-inflammatory cytokines IL-1Î² and IL-6 were significantly down regulated in the challenged-treated group. In conclusion, it is highly recommended to use carvacol and thymol EO either alone or in a combination to improve the body performance and to protect broilers against Campylobacter jejuni.